A Person-Centered Approach toward Balanced Gender Identity in Emerging Adults: Associations with Self-Esteem and Attitudes about Education - Joyce J. Endendijk (MDPI AG, 2023)
Balanced identity theory (BIT) has played an important role in research examining women's underrepresentation in science, technology, engineering, and mathematics (STEM). Yet, BIT's main balanced-congruity principle has not been tested specifically for gender-science cognitions. Additionally, BIT's predictions have been tested primarily from a variable-centered approach. The current study therefore examined whether (1) gender-science cognitions form a balanced identity configuration; (2) different identity profiles can be distinguished; (3) identity profiles differ in background characteristics, study motivation, and self-esteem. Dutch emerging adults (18-25 years old) enrolled in education (N = 318, 51% female) completed a gender-science Implicit Association Test (gender-science stereotypes) and questionnaires assessing felt similarity to males and females (gender identity), interest in science and liberal arts occupations (occupational self-concept), self-esteem, and study motivation and engagement. Hierarchical regression analyses revealed multiplicative interactions between gender-science stereotypes, gender identity, and occupational self-concept, providing evidence for a balanced identity configuration. Furthermore, latent profile analyses revealed three balanced identity profiles and two unbalanced profiles. Unbalanced identity profiles were characterized by non-Dutch ethnicity, lower educational level, and living independently without parents. The identity profiles did not differ in self-esteem and study motivation. Future research should examine the longer term consequences of unbalanced identity for academic and career pursuits.